2021
DOI: 10.3389/fsurg.2021.742328
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Based on Clinicopathological and Ultrasound Imaging Characteristics for Predicting Cervical Lymph Node Metastasis in cN0 Unilateral Papillary Thyroid Microcarcinoma

Abstract: Objective: The aim of this study was to establish a practical nomogram for preoperatively predicting the possibility of cervical lymph node metastasis (CLNM) based on clinicopathological and ultrasound (US) imaging characteristics in patients with clinically node-negative (cN0) unilateral papillary thyroid microcarcinoma (PTMC) in order to determine a personal surgical volume and therapeutic strategy.Methods: A total of 269 consecutive patients diagnosed with cN0 unilateral PTMC by postoperative pathological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…It has been demonstrated that preoperative imaging examination for patients can help physicians make judgments on lymph nodes with typical sonographic features, and perform biopsy during surgery, which can lead to early diagnosis and timely intervention, thereby improving prognosis [17]. HFUS possesses advantages of non-invasion, easy operation, high repeatability, etc., making it the preferred examination method for multiple tissue and organ lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that preoperative imaging examination for patients can help physicians make judgments on lymph nodes with typical sonographic features, and perform biopsy during surgery, which can lead to early diagnosis and timely intervention, thereby improving prognosis [17]. HFUS possesses advantages of non-invasion, easy operation, high repeatability, etc., making it the preferred examination method for multiple tissue and organ lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus critical that risk factors related to CLNM incidence in patients with PTC be better defined in order to guide clinical decision-making. Several studies to date have assessed PTMC(T1a) patients and identified potential clinical and US features associated with CLNM risk, including male sex, younger age multifocality, and extrathyroidal extension, but these findings have not been consistent across studies and analyses of individuals with cT1b stage disease are currently lacking ( 15 – 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced US (CEUS) is a relatively recent technology that can reflect and observe the hemodynamics of normal and diseased tissues. It has high sensitivity and specificity and is a valuable auxiliary examination method ( 5 , 6 ); it has been widely utilized for the evaluation of the liver, kidney, testis, and other parenchymal organs ( 7 ). CEUS can also improve the detection rate of blood vessels in thyroid nodules, particularly tiny blood vessels, which is very critical since angiogenesis is the foundation of tumor formation.…”
Section: Introductionmentioning
confidence: 99%